Scientific opinion concerning the killing of rabbits for purposes other than slaughter. (10th January 2020) - ,; Saxmose Nielsen, Søren; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Depner, Klaus; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortázar Schmidt, Christian; Michel, Virginie; Miranda Chueca, Miguel Ángel; et al.
Abstract: Rabbits of different ages may have to be killed on‐farm for purposes other than slaughter (where slaughter is defined as killing for human consumption) either individually or on a large scale (e.g. for production reasons or for disease control). The purpose of this opinion was to assess the risks associated to the on‐farm killing of rabbits. The processes during on‐farm killing that were assessed included handling, stunning and/or killing methods (including restraint). The latter were grouped into four categories: electrical methods, mechanical methods, controlled atmosphere method and lethal injection. In total, 14 hazards were identified and characterised, most of these related to stunning and/or killing. The staff was identified as the origin for all hazards, either due to lack of the appropriate skill sets needed to perform tasks or due to fatigue. Possible corrective and preventive measures were assessed: measures to correct hazards were identified for five hazards and the staff was shown to have a crucial role in prevention. Five welfare consequences of the welfare hazards to which rabbits can be exposed to during on‐farm killing were identified: not being dead, consciousness, pain, fear and distress. Welfare consequences and relevant animal‐based measures were described. Outcome tables linking hazards, welfare consequences, animal‐based measures, origins, preventive and corrective measures were developed for each process. Mitigation measures to minimise welfare consequences are proposed.